2015
DOI: 10.3389/fphys.2015.00378
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Paratrigeminal Nucleus in Vagal Afferent Evoked Respiratory Reflexes: A Neuroanatomical and Functional Study in Guinea Pigs

Abstract: The respiratory tree receives sensory innervation from the jugular and nodose vagal sensory ganglia. Neurons of these ganglia are derived from embryologically distinct origins and as such demonstrate differing molecular, neurochemical and physiological phenotypes. Furthermore, whereas nodose afferent neurons project to the nucleus of the solitary tract (nTS), recent neuroanatomical studies in rats suggest that jugular neurons have their central terminations in the paratrigeminal nucleus (Pa5). In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 32 publications
6
53
0
1
Order By: Relevance
“…d , tdTomato epifluorescence in adult thoracic DRG. e, f , tdTomato epifluorescence in adult nucleus of the solitary tract (NTS) ( e ) and in adult spinal trigeminal nucleus (Sp5) ( f ), where axons of nodose and jugular/trigeminal sensory neurons project, respectively 52,53 . Smaller panels on right in f show a magnified view of Sp5 with Nefh staining.…”
Section: Extended Datamentioning
confidence: 99%
See 1 more Smart Citation
“…d , tdTomato epifluorescence in adult thoracic DRG. e, f , tdTomato epifluorescence in adult nucleus of the solitary tract (NTS) ( e ) and in adult spinal trigeminal nucleus (Sp5) ( f ), where axons of nodose and jugular/trigeminal sensory neurons project, respectively 52,53 . Smaller panels on right in f show a magnified view of Sp5 with Nefh staining.…”
Section: Extended Datamentioning
confidence: 99%
“…It has been widely reported that nodose sensory neurons contain low-threshold mechanosensors innervating the lower airway tract including the lungs, while jugular sensory neurons contain high-threshold mechanosensors that innervate the upper airway tract, such as the larynx and the trachea. In addition, nodose sensory neurons project to the NTS 6,53 , a synaptic station required for the Hering–Breuer reflex in the brainstem 54 . Consistent with these findings, Piezo2 expression is detected in the jugular–nodose ganglia complex, and Piezo2 + nerve fibres project to the NTS.…”
Section: Extended Datamentioning
confidence: 99%
“…However, selective stimulation of nodose C fibers fails to evoke cough [44]. The mechanisms underlying this disparity are unknown, although recent evidence suggests that jugular and nodose C fibers modulate distinct brainstem networks [50, 51]. …”
Section: Sensory Afferent Nerves Involved In Coughmentioning
confidence: 99%
“…Mazzone and Undem 2016). This nucleus is certainly involved in respiratory reflexes other than cough, such as respiratory slowing and apnea (Chou et al, 2008;Driessen et al, 2015). However, its possible role, if any, in the genesis of the cough motor pattern or of the "urge-tocough" remains to be ascertained.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%